Effect of combined exercise training on heart rate variability in normotensive and hypertensive postmenopausal women - Mariano,Igor M. (2021)
Abstract Aim: This study aimed to verify and compare the effects of 10 weeks of combined exercise training on the heart rate variability of normotensive (NT) and hypertensive (HT) postmenopausal women. Methods: This is a quasi-experimental controlled clinical trial. Therefore, 14 HT and 12 NT postmenopausal women completed 10 weeks of combined exercise training. The exercise protocol consisted of 45 min of exercise, performed 3 times a week, consisting of 5 min of warm-up, 20 min of resistance exercise, and 20 min of aerobic exercise. Heart rate variability assessments were performed before and after the end of physical training. Results: Heart rate variability was assessed pre- and post-training periods. Mean RR (δNT = 95 ± 88; δHT = 38 ± 127), SDNN (δNT = 9 ± 13; δHT = 3 ± 14), RMSSD (δNT = 10 ± 12; δHT = 2 ± 18), SD1 (δNT = 7 ± 8; δHT = 1 ± 13), and SD2 (δNT = 10 ± 18; δHT = 4 ± 17) showed improvements after the intervention (time effects p < 0.05). No parameters presented group or interaction effects (p ≥ 0.05). Conclusion: In summary, 10 weeks of combined exercise training improved heart rate variability parameters similarly in both NT and HT postmenopausal women. Therefore, combined exercise training may be used to improve autonomic modulation of the heart rate of postmenopausal women, regardless of the presence of hypertension.